Dietary Geraniol by Oral or Enema Administration Strongly Reduces Dysbiosis and Systemic Inflammation in Dextran Sulfate Sodium-Treated Mice - De Fazio, Luigia; Spisni, Enzo; Cavazza, Elena; Strillacci, Antonio; Candela, Marco; Centanni, Manuela; Ricci, Chiara; Rizzello, Fernando; Campieri, Massimo; Valerii, Maria C. (Frontiers in Pharmacology, 2016)
(Trans)-3,7-Dimethyl-2,6-octadien-1-ol, commonly called geraniol (Ge-OH), is an acyclic monoterpene alcohol with well-known anti-inflammatory, antitumoral and antimicrobial properties. It is widely used as a preservative in the food industry and as an antimicrobial agent in animal farming. The present study investigated the role of Ge-OH as an anti-inflammatory and anti-dysbiotic agent in the dextran sulphate sodium (DSS)-induced colitis mouse model. Ge-OH was orally administered to C57BL/6 mice at daily doses of 30 and 120mg kg(-1) body weight, starting six days before DSS treatment and ending the day after DSS removal. Furthermore, Ge-OH 120 mg kg(-1) dose body weight was administered via enema during the acute phase of colitis to facilitate its on-site action. The results show that orally or enema-administered Ge-OH is a powerful antimicrobial agent able to prevent colitis-associated dysbiosis and decrease the inflammatory systemic profile of colitic mice. As a whole, Ge-OH strongly improved the clinical signs of colitis and significantly reduced cyclooxygenase-2 (COX-2) expression in colonocytes and in the gut wall. Ge-OH could be a powerful drug for the treatment of intestinal inflammation and dysbiosis.